2014
DOI: 10.5530/ijopp.7.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Prescription practice in patients of upper respiratory tract infection at a pediatric outpatient clinic in Punjab

Abstract: Upper respiratory tract infections (URTI) are the most common and frequently occurring infections in the paediatric population. Often, it has a viral origin and requires only symptomatic treatment. Very few patients require antibiotics. The prescriptions of children, diagnosed with URTI, over one year period of time, were studied to assess the utilization of drugs. Of 2981 patients, only 1078 patients were diagnosed to have URTI. This consisted of 598 male & 480 female patients. It was found that URTI was most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
4
10
3
Order By: Relevance
“…6 In present study 52.61% oral, 30.62% injectable and 16.75% inhalational drugs were prescribed, while in another study 86% drugs were prescribed by oral and 14% by nasal route. 9 Number of drugs per prescription was 8.32 which is in contrast to the study by Gogoi S et al where average number of drugs per prescription was 6.92. 7 In the present study 49.47% drugs from national essential list of medicines 2015 were prescribed, while in previous study 66.7% drugs were prescribed from NLEM.…”
Section: Discussioncontrasting
confidence: 54%
“…6 In present study 52.61% oral, 30.62% injectable and 16.75% inhalational drugs were prescribed, while in another study 86% drugs were prescribed by oral and 14% by nasal route. 9 Number of drugs per prescription was 8.32 which is in contrast to the study by Gogoi S et al where average number of drugs per prescription was 6.92. 7 In the present study 49.47% drugs from national essential list of medicines 2015 were prescribed, while in previous study 66.7% drugs were prescribed from NLEM.…”
Section: Discussioncontrasting
confidence: 54%
“…These results were in agreement with the previous studies where acute respiratory infection such as pneumonia, pharyingitis and fever were important reason for hospitalization and prescription of antibiotics 19,20,21,22 . Our results were in accordance with Tiwari et al, who showed that 80% 23 25 respectively. However, in a study carried out in 50 primary health care centers (PHCCs) across 5 governorates of Kuwait, the mean number of drugs prescribed per prescription was 2.9 26 and in 4 PHCCs of Bahrain, the average number of drugs per encounter was 2.6 6 .…”
Section: Study Population and Data Collectionsupporting
confidence: 93%
“…In present study the most common diseases were chronic obstructive pulmonary disease (COPD), Bronchial asthma, Pneumonia and upper respiratory tract infections (URTIs), which is similar to the previous studies [20][21][22].…”
Section: Gendersupporting
confidence: 78%